Budaya Berbagi Ruang Kehidupan dan Kemajemukan Hukum Masyarakat Mamberamo Raya - Mambiew, Albertus Oskar; Frank, Simon Abdi K.; Yuliana, Yuliana (CENDERAWASIH: Jurnal Antropologi Papua, 2023)
This research aims to analyse the culture of sharing space and strategies in dealing with multicultural spatial arrangements in Mamberamo Raya Regency and to analyse the legal progress of the Mamberamo Raya community as an implication of the existence of sharing living space. This research uses a qualitative research method with an ethnographic approach. data collection techniques are interviews, observation, and documentation. Data analysis includes the stages of domain analysis, taxonomy analysis, componential analysis and cultural theme analysis. The results showed that the sharing of living space in local communities in Mamberamo Raya are: material meaningful space; historical meaningful space; religious meaningful space; educative meaningful space; economic meaningful space. The narrowing of the boundaries of living space in the conception of each ethnicity in Mamberamo Raya makes 'some' local ethnicities continue to try to be resistant with all the power they have. This occurs because of the desire to continue to maintain their respective cultures and the desire to continue to live together peacefully. The sharing of living space between local communities and migrants in Mamberamo Raya is largely determined by the legal institutions of each community that work together. As an alternative to solving the problem of inter-ethnic struggle for living space in Mamberamo Raya, it is necessary to have a deeper understanding of the function and role of law in people's lives.